In Situ Synthesis of Gold Nanostars within Liposomes for Controlled Drug Release and Photoacoustic Imaging - Mathiyazhakan, Malathi (2016)
This report describes the design and synthesis of gold nanostars (AuNSs) containing liposomes by the in situ reduction of gold precursor, HAuCl4 (pre-encapsulated within the liposomes) through HEPES diffusion and reduction. Compared with the conventional process that encapsulates the pre-synthesized gold nanoparticles into liposomes during the thin-film hydration step, this facile and convenient method allows the formation and simultaneous encapsulation of AuNSs within liposomes. The absorption spectra of AuNSs can be tuned between visible and near infra-red (NIR) regions by controlling the size and morphology of AuNSs through varying the concentrations of HAuCl4 and HEPES. As a proof of concept, we demonstrate the synthesis of AuNSs with a maximum absorbance at 803 nmwithin the temperature-sensitive liposomes. These liposomes can produce stronger photoacoustic signals (1.5 fold) in the NIR region than blood. Furthermore, when there are drugs (i.e., doxorubicin) within these liposomes, the irradiation with the NIR pulse laser will disrupt the liposomes and trigger the 100% release of these pre-encapsulated drugs within 10 seconds. In comparison, there is neglectable contrast enhancement or minor release (10%) of drugs for the pure liposomes under the same conditions. Finally, cell experiment shows the potential therapeutic application of this system.